Silver-polymer core-shell nanoparticles for ultrastable plasmon-enhanced photocatalysis - Asapu, Ramesh; Claes, Nathalie; Bals, Sara; Denys, Siegfried; Detavernier, Christophe; Lenaerts, Silvia; Verbruggen, Sammy W. (Applied catalysis. B, Environmental, 2017)
[Display omitted] •Ag-polymer-TiO2 composites show ultrastable photocatalytic activity in the long term.•Ag-polymer core-shell nanoparticles prepared using affordable layer-by-layer method.•Thin polymer shell prevents oxidation and clustering of the silver nanoparticles.•Finite element simulations show retention of plasmonic near-field enhancement. Affordable silver-polymer core-shell nanoparticles are prepared using the layer-by-layer (LbL) technique. The metallic silver core is encapsulated with an ultra-thin protective shell that prevents oxidation and clustering without compromising the plasmonic properties. The core-shell nanoparticles retain their plasmonic near field enhancement effect, as studied from finite element numerical simulations. Control over the shell thickness up to the sub-nanometer level is there for key. The particles are used to prepare a plasmonic Ag-TiO2 photocatalyst of which the gas phase photocatalytic activity is monitored over a period of four months. The described system outperforms pristine TiO2 and retains its plasmonic enhancement in contrast to TiO2 modified with bare silver nanoparticles. With this an important step is made toward the development of long-term stable plasmonic (photocatalytic) applications.